Aripiprazole disrupts cellular synchrony in the suprachiasmatic nucleus and enhances entrainment to environmental light–dark cycles in mice - Li, Ruoshi; Masuda, Kosaku; Ono, Daisuke; Kanbayashi, Takashi; Hirano, Arisa; Sakurai, Takeshi (Frontiers in Neuroscience, 2023)
Many patients with psychiatric conditions, such as bipolar disorder and major depressive disorder, frequently experience disruptions in their sleep–wake cycles. Several case studies and clinical trials have shown that the administration of aripiprazole, a commonly prescribed antipsychotic drug, alleviates the symptoms of circadian sleep disorders in these patients. This improvement may be attributed to the effects of aripiprazole on the circadian central clock, specifically the hypothalamic suprachiasmatic nucleus (SCN), which regulates various circadian physiological rhythms, including the sleep–wake cycle, in mammals. To examine whether aripiprazole facilitates adaptation to changes in the light–dark cycle, we orally administered aripiprazole to mice and subjected them to jet-lag experiments. Mice receiving aripiprazole were more rapidly entrained to 6 h advanced light–dark cycles. Moreover, we examined the effect of aripiprazole on the cellular rhythms of SCN slice cultures and found that aripiprazole disrupted cellular synchronization in the SCN, thereby accelerating the damping of the SCN rhythm at the population level. Adenosine 3′5’ monophosphate (cAMP) assay using a bioluminescence indicator revealed that intracellular cAMP level in the SCN increased following aripiprazole treatment. However, this increase was blocked by pre-treatment with the serotonin 1A receptor (5-HT1AR) antagonist. Based on these findings, we propose that aripiprazole modulates intracellular signaling, including 5-HT1AR-mediated cAMP signaling, and desynchronizes SCN neurons, ultimately leading to enhanced entrainment to phase advanced light–dark cycles in mice. These findings indicate that the improvement in sleep symptoms reported in patients with psychiatric disorders receiving aripiprazole may be due to modulation of the circadian clock. Our study provides novel insights into the potential clinical applications of aripiprazole in patients with various circadian sleep disorders.